Accessing 2‐Arylbenzofurans by CuI2(pip)2‐Catalyzed Tandem Coupling/Cyclization Reaction: Mechanistic Studies and Application to the Synthesis of Stemofuran A and Moracin M1. Issue 11 (15th September 2016) - Qin, Dan‐Dan; Chen, Wei; Tang, Xiao; Yu, Wen; Wu, An‐An; Liao, Yi; Chen, Hong‐Bin
Abstract: An asymmetric dinuclear copper(I) complex, Cu I 2 (pip)2 (pip=(2‐picolyliminomethyl)pyrrole anion), was used to catalyze the tandem coupling/cyclization reaction of o ‐iodophenols and terminal alkynes, which led to the formation of valuable 2‐arylbenzofurans in good yields. DFT calculations showed that the two proximate copper atoms play cooperative roles throughout the catalytic cycle. Using this catalytic protocol, bioactive natural products stemofuran A and moracin M were concisely synthesized. Abstract : Just a pip : An easily available dinuclear copper(I) complex, Cu I 2 (pip)2 (pip=(2‐picolyliminomethyl)pyrrole anion), was used to catalyze the tandem coupling/cyclization reaction of o ‐iodophenols and terminal alkynes, which led to the formation of valuable 2‐arylbenzofurans in good yields. DFT calculations showed that the two proximate copper atoms play cooperative roles throughout the catalytic cycle. Using this catalytic protocol, bioactive natural products stemofuran A and moracin M were concisely synthesized.